Genetic variability and population structure of two sympatric cownose rays Rhinoptera (Myliobatiformes, Rhinopteridae) in the Western Atlantic Ocean - Barreto, Paola Palacios; Mendoza-Portillo, Verónica; Adams, Douglas H.; Cruz, Vanessa P. [UNESP]; Foresti, Fausto [UNESP]; Díaz-Jaimes, Píndaro (PeerJ, 2024)
Cownose rays Rhinoptera bonasus and R. brasiliensis, are species distributed along the coastal waters from eastern United States, Gulf of Mexico to Brazil. This study represents the most extensive evaluation to date of the genetic diversity and population genetic structure of R. bonasus across its distribution, and it is the first to investigate the population genetics of R. brasiliensis. We analyzed sequences of COI and Cytb genes for Rhinoptera bonasus (COI: 230, Cytb: 108) and R. brasiliensis (COI: 181, Cytb: 105) to investigate the genetic diversity and their relationship with environmental variables, genetic structure, as well as demographic parameters. We found that benthic temperature and current velocity were the most important environmental variables in genetic diversity. The global population structure reveals the presence of significant population genetic structure in both species. Bayesian clusters in BAPS were consistent with the segregation pattern observed for haplotype networks based on COI and Cytb markers for both species, which may respond to philopatry and temperature. These results will further improve management and conservation efforts for theses species of ecological and economic importance.
Keywords: Conservation genetics; Environmental association; Gene divergence; Gene diversity; Phylogeography